Analisa Drainase Untuk Penanggulangan Banjir Pada Ruas Jalan Garuda Sakti Di Kota Pekanbaru Menggunakan Software HEC-RAS - Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Drainage system in Garuda Sakti street is not functioning optimally. It can be seen from the innability of drainage channels in the siphon discharge runoff. Floods cause traffic congestion and then disturbed teaching and learning activities in elementary school around the location of research. Analysis of floods was done with analyzing the drainage channels capacity and comparing it with the calculated discharge using Rasional method. The analysis of drainage capacity was conducted by using HEC-RAS version 4.1.0. Drainage geometrical analysis performed on the two types of simulations with three types time period, such as five years, ten years and twenty two years. The results on the existing condition is the maximum depth of floods is 14,30 centimeters for the five years time period, 16,40 centimeters for the ten years time period and 17,40 centimeters for the twenty years time period. Normalization with excavation depth of the channels can flood prevention and tackling effort is maximal.Key words: Flood, the rational formula, HEC-RAS